A-1: THE ALLEGED BELIEF OF RETURN (RAJ'A) IN TWELVER SHIA THEOLOGY OVERVIEW AND CRITIQUE: عقيدة الرَّجْعَة المزعومة عند الإمامية الاثني عشرية عرضٌ ونقدٌ - Shah, Abdul Rahman; Balakhi, Mohammad Ismail Labib (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2023)
One of the most important principles of belief is faith in the Day of Judgment, where Allah gathers creatures and nations for reckoning and reward, unlike any other time. Among the derivatives of this belief is the firm belief that the deceased does not return to the world after departing from it. The Quran and the Sunnah do not mention any return or resurrection except on the Day of Judgment. However, the Twelver Shia sect claims otherwise and asserts the return of the Imams from the House of the Prophet before the Day of Judgment during the time of their presumed Mahdi. This claim is aimed at seeking revenge from their enemies and opponents, particularly notable companions such as the two sheikhs and Aisha, the mother of the Believers. The first to introduce this belief in the Islamic community was the cunning Jew Abdullah bin Saba, who feigned conversion to Islam to undermine it from within. He transferred such beliefs filled with hatred, enmity, and animosity from the religion of his Jewish ancestors to Islam. The Jews believe in the return of some of their enemies and adversaries to the world after departing from it during the time of their supposed Messiah for revenge and retaliation. This belief was adopted by the followers of Abdullah bin Saba, known as the Saba'is, and from them, it reached various Imami factions. It became firmly rooted within the Twelver Shia sect, to the extent that those who oppose it are considered to be enemies of their sect. This belief is fundamentally false and baseless, contradicting the teachings of the Quran and Sunnah, the statements of scholars, and the proofs of reason. The fact that its originator is the deceitful Jew Abdullah bin Saba, who aimed to ignite discord among Muslims by propagating false beliefs and casting doubt on the core tenets of their faith, is sufficient evidence of its invalidity and corruption. Another aspect of its invalidity is that it is built upon fictitious and false beliefs, such as the claim that the first three caliphs usurped the right of Ali ibn Abi Talib to the caliphate. Additionally, their mythological belief in their presumed Mahdi, who does not actually exist, is another reason for its invalidity and corruption. It is well known that anything built upon lies, illusions, and fantasies is inherently flawed and corrupt.